S123 The effect of rhinovirus infection on cough receptors on human sensory nerve and human primary bronchial epithelial cells. (2nd December 2011) - Abdullah, H; Cosby, S L; Heaney, L; McGarvey, L
Abstract : Human rhinovirus (HRV), a member of the picornaviridae family is a single stranded RNA virus. Rhinovirus infection in non-asthmatics rarely causes serious problems. However in asthmatic subjects HRV contributes to more than 60% of asthma exacerbations where the cough reflex is hyper-reactive and provokes severe coughing and wheezing. Rational: Members of a novel transient receptor potential (TRP) channels, the TRP vanilloid 1 (TRPV1), ankyrin like protein with transmembrane like domain 1 (TRPA1) and TRP melastatin 8 (TRPM8) have been shown to be involved in physiological and pathological aspects of cough. Subsequently understanding the interaction between HRV and 'cough receptors' is crucial as it may indicate potential therapeutic targets and strategies to block these interactions. In this study we investigated the effect of HRV infection on the cough reflex by determining the expression of receptors implicated in the cough process. We hypothesised that HRV may directly and/or indirectly interact with these receptors on sensory nerves and epithelial cells in the airways to provoke cough reflex. Methods: Human primary bronchial epithelial cells (PBEC) were obtained following informed consent and the human neuroblastoma (IMR-32) cell line was used to represent the fundamental cell type which controls the reflex to cough. The IMR-32 cells undergo differentiation (dIMR-32) to acquire characteristics of peripheral nerve cells with positive neuronal markers. The expression of 'cough receptors' at the protein level in both cell types were detected by fluorescent staining using confocal microscopy and flow cytometry analysis. Receptors mRNA levels were measured by quantitative real-time PCR at different time points post-infection with HRV or treatment with UV-inactivated virus or supernatant. Results: Both cell types dIMR-32 and PBEC were susceptible to HRV infection and showed positive staining for TRPA1, TRPV1 and TRPM8. Up-regulation of the 'cough receptors' mRNA occurred at low multiplicity of infection moreover, higher level of 'cough receptors' expression was detected in PBEC isolated from subjects with lung disease compared to healthy volunteers. Conclusions: These results suggest that virus may both induce cough and interfere with cough related airway clearance depending on the level of infection at different time points.